Untersuchung der Lithosphäre des Dronning Maud Lands, Antarktis, mit geophysikalischen Methoden - Bayer, Bettina (Univ. Bremen, 2008)
Antarctica, Dronning Maud Land, anisotropy, seismic anisotropy, shear wave splitting, receiver functions, moho, moho depth, crust, upper mantle, refraction seismic, gravity, 3D-gravity, igmas, bouguer anomaly, seismology. - The area of investigation, Dronning Maud Land (DML), comprises with the Weddell Sea and the Lazarev Sea approximately the region between 15 degrees W and 15 degrees E longitude and 68 degrees and 75 degrees latitude - a surface area of more than 1.500.000 qkm. Three major events formed the present-day geology and tectonic settings of DML: (1) the Grenvillian Orogeny, ca. 1.1 Ga ago, caused by the formation of the supercontinent Rhodinia, (2) the Panafrican Orogeny 500 Ma ago, forming the supercontinent Gondwana due to the collison of West and East Gondwana, and (3) the break-up of Gondwana 180 Ma ago, which started in the present-day Lazarev Sea. Seismological, refraction seismic and aerogravity data-sets form the basis of this thesis. The combination of these data-sets allows to investigate the structural composition and the spatial variation of the lithospheric thickness. The latter is essential for the determination of the regional geoid, which is the main objective of the VISA-project. Within the framework of this project airborne measurements of the potential field as well as ice-penetrating radar and GPS-measurements have been carried out. Moreover, seismographic stations were temporarily deployed in various parts of DML. Despite their very short operation time, applications of seismological methods to the recorded teleseismic events yielded conclusions about the structure and dynamic of the deeper subsurface. By analyses of seismic anisotropy, which investigates the splitting of shear waves traversing an anisotropic medium (so-called shear wave splitting) conclusions ... : thesis